2022
DOI: 10.1016/j.envres.2022.112806
|View full text |Cite
|
Sign up to set email alerts
|

Changes in stoichiometric characteristics of ambient air pollutants pre-to post-COVID-19 in China

Abstract: To prevent the Corona Virus Disease 2019 (COVID-19) spreading, Chinese government takes a series of corresponding measures to restrict human mobility, including transportation lock-down and industries suspension, which significantly influenced the ambient air quality and provided vary rare time windows to assess the impacts of anthropological activities on air pollution. In this work, we divided the studied timeframe (2019/12/24–2020/2/24) into four periods and selected 88 cities from 31 representative urban a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
9
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(9 citation statements)
references
References 27 publications
0
9
0
Order By: Relevance
“…The epidemic control measures significantly reduced the NO 2 /SO 2 ratio by 1.11 (95%CI: 0.81–1.42) in the T C period and 0.02 (95%CI: −0.38–0.41) in the T B period ( Fig. 4 ), which was largely due to the fact that mobile sources such as transport, represented by NO 2 in Lanzhou, decreased more but at concentrations several times higher than SO 2 , causing a less than expected decrease than in other areas for this ratio ( Bai et al, 2022 ). Moreover, this ratio increased with COVID-19 lockdown during the T A period, mainly due to the “challenges in the resumption of work and production”, triggering a sharp short-term decline in SO 2 instead of an increase in NO 2 .…”
Section: Results and Interpretationsmentioning
confidence: 86%
See 1 more Smart Citation
“…The epidemic control measures significantly reduced the NO 2 /SO 2 ratio by 1.11 (95%CI: 0.81–1.42) in the T C period and 0.02 (95%CI: −0.38–0.41) in the T B period ( Fig. 4 ), which was largely due to the fact that mobile sources such as transport, represented by NO 2 in Lanzhou, decreased more but at concentrations several times higher than SO 2 , causing a less than expected decrease than in other areas for this ratio ( Bai et al, 2022 ). Moreover, this ratio increased with COVID-19 lockdown during the T A period, mainly due to the “challenges in the resumption of work and production”, triggering a sharp short-term decline in SO 2 instead of an increase in NO 2 .…”
Section: Results and Interpretationsmentioning
confidence: 86%
“…Previous studies have also used the NO 2 /SO 2 ratio to account for the contribution of mobile and stationary sources to air pollution ( Bai et al, 2022 ). High and low NO 2 /SO 2 ratios indicate high contribution from mobile and stationary sources, respectively.…”
Section: Results and Interpretationsmentioning
confidence: 99%
“…Exploring the change in the proportional relationship of different pollutant concentrations can determine the source or type of pollutants, which helps to improve the accuracy of pollution control. PM 2.5 and PM 10 have different physical and chemical properties, and previous studies have revealed that the ratio of PM 2.5 /PM 10 can indirectly provide some indicators, such as pollutant composition, source contribution, and impact on health [124][125][126][127][128]. Overall, a lower PM 2.5 /PM 10 ratio demonstrate a predominance of PM 10 (mainly from natural sources), and a higher ratio indicates more air pollution from anthropogenic sources [124][125][126].…”
Section: Pm 25 /Pm 10 Ratiomentioning
confidence: 99%
“…Pollutant concentrations in ambient air have been measured and regulated for many decades now, to prevent negative effects of air pollution to health and the environment [1]. Evidence on adverse effects of ambient air pollution has been mounting steadily, and public interest in the quality of the air we breathe has been on the rise especially since the outbreak of COVID-19 pandemic [2,3]. While until recently, monitoring of air quality has been done by professional agencies, today, the availability of portable, low cost microsensor devices and the exponential growth of IoT (Internet of Things) in everyday life has enabled widespread monitoring of air quality also by lay people [4,5].…”
Section: Introductionmentioning
confidence: 99%